Women, Gender and the evolving tactics of Boko Haram - Elizabeth Pearson (Journal of Terrorism Research, 2014)
This article addresses an under-researched aspect of Boko Haram’s activities: gender-based violence (GBV) and its targeting of women. It argues that 2013 marked a significant evolution in Boko Haram’s tactics, with a series of kidnappings, in which one of the main features was the instrumental use of women. This was in response to corresponding tactics by the Nigerian security forces. Additionally the analysis provides evidence of a shift by Boko Haram to include women in its operations, in response to increased pressure on male operatives. It also considers the gendered rationale for instrumentalizing women within the framework of Boko Haram’s ideology and culture, arguing for a greater appreciation of how gender factors in the group’s violence.